Mixed Ligand Complexes of Co(II), Ni(II) and Hg(II) Diphenates with Amine Bases (Biological Sciences - PJSIR, 2022)
Agafonova and Ryuzanov f 1,21 curried out the prccipitationand separation studies of Fe+2, Mn+2, Co+2, Ni+2 and Zn+2.Diphcnic acid has also been used [31 us u selective reagent forthcumpcromctric dctcrmlnution of thorium (IV).